Adherence of Pseudomonas aeruginosa to human tracheobronchial mucin. - Vishwanath, S (1984)
A microtiter plate assay was developed to study the adherence of Pseudomonas aeruginosa to purified human tracheobronchial mucin. The wells of the plates were treated with silicon to minimize nonspecific binding of bacteria and then coated with a solution of purified human tracheobronchial mucin. Bacteria were added to the wells, and the plates were incubated at 37 degrees C. The wells were washed 15 times in an automated microtiter plate washer, and the bacteria bound to wells were desorbed with Triton X-100 and plated for enumeration. Scanning electron microscopy verified bacterial adherence to the mucin-coated wells and desorption of bacteria by Triton X-100. Adherence of P. aeruginosa increased as the concentration of mucin used to coat the wells was increased, with saturation occurring at 0.5 microgram of mucin protein per ml. Other parameters that affected adherence included the time of incubation and concentration of bacteria. Similar studies with strains of Escherichia coli and Klebsiella pneumoniae indicated a relative lack of binding of these bacteria to mucin. In comparing different strains of P. aeruginosa, there were small differences in binding between strains. It is inferred that there may be specific sites on human tracheobronchial mucin which facilitate this preferential binding.